2023
DOI: 10.1007/s00404-023-07003-x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid umbilical cord blood banking: literature review

Abstract: Purpose Interest gaps between public and private umbilical cord blood banks have led to the introduction of hybrid banking options. Hybrid models combine features of private and public banks as well as interests of parents, children and of patients, in order to find an optimized solution. While several different models of hybrid banks exist, there is a lack of literature about this novel model of cord blood stem cell banking. Therefore, the aim of this literature review is to assess different opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Prior to this survey, a systematic literature review was performed, which showed great potential for hybrid CB banking as an alternative to the pre-existing banking methods. 7 No study however addressed the women's perspectives on an available hybrid banking model.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this survey, a systematic literature review was performed, which showed great potential for hybrid CB banking as an alternative to the pre-existing banking methods. 7 No study however addressed the women's perspectives on an available hybrid banking model.…”
Section: Discussionmentioning
confidence: 99%